The Role of System Trust and Risk Perception in Providing Assets for Collaborative Consumption Schemes. - Decrop, A.
The emergence of the sharing economy has fueled the development of collaborative consumption (CC) schemes around the world. The promise of non-ownership particularly in the peer-to-peer environment makes it attractive for a plethora of users to engage in practices such as carsharing and the rental of private holiday accommodations or tool supply from their peers. Yet while financial and environmental benefits for both users and providers do exist, providers of private goods may be reluctant in many cases to offer their belongings for sharing. This study thus draws on social exchange theory to examine the key role of generalized, barterand money-balanced reciprocity as a pivotal scheme characteristic that predicts the intention of providers to participate in peer-to-peer CC schemes. As such, the findings from two empirical studies provide evidence that consumers are most eager to provide their personal assets against a reciprocal compensation where perceived risk functions as a mediator of the explained effect. Market mediation is also used to show that CC schemes are more attractive to consumers when facilitated by a non-profit market intermediary (vs. a for-profit intermediary), emphasizing the propensity of consumers to escape the market while sharing. A mechanism in which system trust mediates the proposed relationships is therefore suggested.